Abstract

No abstract available.

Full Article  |  PDF Article

Corrections

Marvin R. Querry, "Errata: Direct Solution of the Generalized Fresnel Reflectance Equations," J. Opt. Soc. Am. 60, 705_1-705 (1970)
https://www.osapublishing.org/josa/abstract.cfm?uri=josa-60-5-705_1

References

  • View by:
  • |
  • |
  • |

  1. D. G. Avery, Proc. Phys. Soc. (London) B65, 425 (1952).
  2. W. R. Hunter, J. Opt. Soc. Am. 55, 1197 (1965).
    [CrossRef]
  3. R. Tousey, J. Opt. Soc. Am. 29, 235 (1939).
    [CrossRef]
  4. M. Querry, “Infrared Reflectance of Water,” Ph.D. dissertation, Kansas State University (1968).

1965 (1)

1952 (1)

D. G. Avery, Proc. Phys. Soc. (London) B65, 425 (1952).

1939 (1)

Avery, D. G.

D. G. Avery, Proc. Phys. Soc. (London) B65, 425 (1952).

Hunter, W. R.

Querry, M.

M. Querry, “Infrared Reflectance of Water,” Ph.D. dissertation, Kansas State University (1968).

Tousey, R.

J. Opt. Soc. Am. (2)

Proc. Phys. Soc. (London) (1)

D. G. Avery, Proc. Phys. Soc. (London) B65, 425 (1952).

Other (1)

M. Querry, “Infrared Reflectance of Water,” Ph.D. dissertation, Kansas State University (1968).

Cited By

OSA participates in CrossRef's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Equations (16)

Equations on this page are rendered with MathJax. Learn more.

R = ( Q - cos θ ) 2 + P 2 ( Q + cos θ ) 2 + P 2
R = R ( Q - sin θ tan θ ) 2 + P 2 ( Q + sin θ tan θ ) 2 + P 2 ,
Q 2 - P 2 = n 2 - k 2 - sin 2 θ
Q P = n k .
n = { 1 2 [ - P 2 + Q 2 + sin 2 θ + ( ( P 2 - Q 2 - sin 2 θ ) 2 + 4 P 2 Q 2 ) 1 2 ] } 1 2 .
P 2 = - Q 2 - 2 F Q cos θ - cos 2 θ ,
F = ( R + 1 ) / ( R - 1 ) .
Q = ( G - F ) sin θ cot 2 θ G F + ( 1 - F 2 ) cos 2 θ - 1 ,
G = ( R + 1 ) / ( R - 1 ) .
D = ( R + - R - ) / m , D = ( R + - R - ) / m ,
D θ = ( θ + - θ - ) / m ,
R r = R - + r D , R s = R - + s D ,
θ t = θ - + t D θ ,
r , s , t = 0 , 1 , 2 , , m .
F s = ( R s + 1 ) / ( R s - 1 ) , G r = ( R r + 1 ) / ( R r - 1 ) , Q r s t = ( G r - F s ) sin θ t cot 2 θ t G r F s + ( 1 - F s 2 ) cos 2 θ t - 1 , P r s t 2 = - Q r s t 3 - 2 F s Q r s t cos θ t - cos 2 θ t , Y r s t = ( - P r s t 2 + Q r s t 2 + sin 2 θ t ) / 2 , n r s t = [ Y r s t + ( Y r s t 2 + P r s t 2 Q r s t 2 ) 1 2 ] 1 2 , k r s t = ( P r s t Q r s t ) / n r s t , n = 1 ( m + 1 ) 3 r , s , t = 0 m n r s t ,
k = 1 ( m + 1 ) 3 r , s , t = 0 m k r s t .